Effects of creatine supplementation on sprint performance in youth, elite football players - Horne, S.; Simpson, A. J.; Sharp, P.; Farrier, G.; Sharps, R.; Kippelen, P. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Creatine is a highly popular food supplement in football (Waddington et al., 2005). Whilst a wealth of data exists on the ergogenic effects of creatine supplementation in senior players, limited data are available in youth players. Therefore the aim of this study was to examine the effects of a standard, 8wk course of oral creatine monohydrate (CM) supplementation on sprint performance in youth, elite football players. Methods: Fifteen U18 (age 16 to 18 yr), male, Football Academy players followed a randomised, double-blind, placebo-controlled, parallel-group trial during the early competitive season. Players ingested 0.3 g/kg/d of CM (n=7) or placebo (PLA, n=8) during a 1wk loading phase, followed by 5 g/day of CM or placebo during a 7wk maintenance phase. Pre- and postsupplementation participants underwent body composition assessment (via body mass and sum of 8 skinfold thicknesses) and performed a repeated-sprint ability (RSA) test (Rampinini et al., 2009). In a subgroup of 10 outfield players (4 on CM and 6 on PLA), GPS data were obtained during match play in the period leading to the supplementation period and in weeks 4 to 8 of the supplementation period. Key index of sprint performance was % of overall match distance covered at >19 km/h (Osgnach et al., 2010). Data are presented as mean +/-SD, compared by RM-ANOVA. Results: Body mass did not significantly change over the course of supplementation in either group. A small but significant (P=0.007) decrease in skinfold thickness was observed post-supplementation, with no group difference (-7+/-4% in CM and -5+/-8% in PLA). RSA did not significantly improve post-supplementation (mean RSA time pre- vs postsupplementation: 7.57+/-0.18 vs 7.52+/-0.22 sec in CM; 7.44+/-0.30 vs 7.24+/-0.18 sec in PLA). Sprint performance during competitive match play did not significantly differ pre- to post-supplementation, or between groups (overall match distance covered at >19 km/h: pre 4.8+/-0.7 and post 5.6+/-1.6% in CM vs pre 7.3+/-2.8 and post 7.2+/-2.9% in PLA). Discussion: In youth, elite players 8wk of CM supplementation did not induce muscle mass gain beyond that observed with training alone. Further, CM did not significantly improve sprint performance. Thus these findings cast doubt about the effectiveness of CM as an ergogenic aid in youth, elite football.